Portable Solar Charger System with Energy Measurement and Access Control - Erwin Sitompul; Angga Febian; Antonius Suhartono (Jetri : Jurnal Ilmiah Teknik Elektro, 2022)
The utilization of green energy is one trending issue in the current time. People try to increase the portion of energy gained from renewable sources such as wind, solar, hydro, and geothermal energy. In this paper, the authors propose a portable solar charger system (PSCS) that can be used to charge cellular devices when electricity access is not available such as during a power shutdown or when traveling to remote locations. The PSCS is made compact in two parts: the solar panel and the utility box, making the whole system easy to carry. The energy obtained from the solar panel is stored in a dry battery, with the process carefully regulated by a solar charge controller. The PSCS is equipped with passcode protection and gained energy monitor. The electric current from the battery flows to the load through a DC-DC converter and a relay only if a correct passcode is entered via a keypad. The amount of gained energy by the solar panel is monitored by measuring the voltage across the panel and the current flowing through its circuit. The functionality of the PSCS is successfully tested. Eight experiments each with a 3-hour duration are conducted on 6 different days. The amount of gained energy varies from 5.26 Wh to 9.88 Wh (1,300 mAh to 2,670 mAh), which corresponds to 14.5 % and 31.5 % of the potential average daily output energy for the location of Cikarang, Indonesia.